HUBUNGAN KEBIASAAN MENGKONSUMSI MINUMAN BERENERGI DENGAN STATUS DIABETES MELITUS TIPE 2 PADA SOPIR TAKSI DI KOTA PONTIANAK - Salim, Maulidiyah; Afni, Adisty; Sari, Emilda (EMPIRIS : Jurnal Sains, Teknologi dan Kesehatan, 2024)
Diabetes is one of the leading non-communicable diseases causing mortality worldwide. Type 2 diabetes mellitus is characterized by elevated blood sugar levels due to insulin dysfunction, influenced by behaviors such as energy drink consumption. This study aims to examine the relationship between energy drink consumption habits and type 2 diabetes mellitus status among taxi drivers in Pontianak City.This research employed a cross-sectional design involving 31 taxi drivers as participants. Data collected through interviews revealed that among respondents consuming energy drinks ≤4 times per week, 64.51% were in the normal category with no prediabetes cases. Conversely, in the group consuming >4 times per week, 12.90% were in the normal category, and 22.58% in the prediabetes category. Bivariate analysis using the Chi-square test demonstrated a significant relationship between energy drink consumption habits and type 2 diabetes mellitus status (p-value 0.001 < α 0.005). These findings indicate that the frequency of energy drink consumption contributes to type 2 diabetes mellitus status among taxi drivers in Pontianak City.